Pengaruh Nilai Kurs, Deviden Price Ratio dan Price Book Value terhadap Return Saham pada PT Sampoerna Argo Tbk Periode 2007-2017 - Tiarah Tiarah (Science of Management and Students Research Journal (SMS), 2019)
This study aims to analyse the influence of the value of exchange rate, Dividend Payout Ratio and Price book value simultaneously against the Return of shares and analyze the effect of the exchange rate, the value of the Dividend Payout Ratio and Price Book partially against the Return of shares . This research uses descriptive method quantitative efeksional research with the form that describes the relationship of the influence of free variables with variables bound. The research on the analysis tools using multiple linear regression with hypothesis prove with statistical tests of the F test statistic t &. The results showed that the value of the exchange rate, Dividend Payout Ratio and Price book value effect significantly to The stock price where marked with Fhitung > Ftabel and prog. sig < alpha (0.05). While the value of the coefficient of determination (R2) is 54% of these means that the relations very closely between the independent  variable of effect variable with the stock price. While partially does not exist its influence on Stock Return.